Developing Skills in Veteran-Centered Care: Understanding Where Soldiers Really Come From - Monica Lypson; Divy Ravindranath; Paula Ross (Association of American Medical Colleges, 2014)
Abstract Introduction This workshop was created to improve care for the nearly 2.6 million US service members returning from Iraq and Afghanistan, and other veterans who served in the past. Improving clinical care training for veterans' care has become a matter of national attention and has also gained increasing attention from the medical community. Methods This workshop is designed to last approximately 90 minutes and will assist faculty in facilitating discussions on veteran-centered care as well as mental illness in US veterans. Upon viewing scenes from the award-winning movie Where Soldiers Come From, participants will engage in active discussion sessions in which they reflect on their impressions of the clips, situations, and themes from each scene. They will be asked to discuss the issues that arise in each scene as the basis for exploration of their own personal and professional experiences and identities. They will also discuss ways to engage their learners in this issue as it relates to engaging trainees on related topics. This packet provides comprehensive guidelines for conducting a multistage faculty development workshop for veteran-centered care. The objectives provided as well as the exercises allow for outcome measurement. Results To date, this workshop has been delivered with primary care providers, both physicians N = 27; nurses N = 3; and psychologist N = 1 in VA settings (6 participants did not list their role). Participants were from various medical specialties (internal medicine, family medicine, clinical health psychiatry, preventative medicine, and surgery). Responses to the evaluation of the workshop are as follows: Participant gained a better understanding of veterans and their care skills-26 (70.2%) indicated agree/strongly agree; participant were able to identify key issues in veterans and their care- 9 (78.3%) indicated agree/strongly agree; participant gained a better understanding of how to prepare for issues around the returning veterans-27 (72.9%) indicated agree/strongly agree; scenes from the documentary helped participant to reflect on their own attitudes toward veterans-33 (89.2%) indicated agree/strongly agree. Discussion In order to provide this workshop, the facilitator is encourage to buy an educational license for use of the documentary. This means that resources for the purchase of the DVD and ideally some audio visual assistance are needed. Of note, sufficient protected time should be garnered for the delivery of this workshop as it takes the full amount of time listed.